Elevated CO2 degassing rates prevented the return of Snowball Earth during the Phanerozoic. Issue 1 (December 2017) - Mills, Benjamin; Scotese, Christopher; Walding, Nicholas; Shields, Graham; Lenton, Timothy
Abstract The Cryogenian period ( 720–635 Ma) is marked by extensive Snowball Earth glaciations. These have previously been linked to CO2 draw-down, but the severe cold climates of the Cryogenian have never been replicated during the Phanerozoic despite similar, and sometimes more dramatic changes to carbon sinks. Here we quantify the total CO2 input rate, both by measuring the global length of subduction zones in plate tectonic reconstructions, and by sea-level inversion. Our results indicate that degassing rates were anomalously low during the Late Neoproterozoic, roughly doubled by the Early Phanerozoic, and remained comparatively high until the Cenozoic. Our carbon cycle modelling identifies the Cryogenian as a unique period during which low surface temperature was more easily achieved, and shows that the shift towards greater CO2 input rates after the Cryogenian helped prevent severe glaciation during the Phanerozoic. Such a shift appears essential for the development of complex animal life. Despite dramatic changes in carbon sinks, severe Snowball Earth glaciations have not occurred since the Cryogenian. Here, via the measurement of global subduction zone lengths and carbon cycle modelling, the authors show that a two fold increase in volcanic CO2 input likely thwarted global glaciation.